Robotic microscopy for everyone: the OpenFlexure microscope - Collins, Joel T.; Knapper, Joe; Stirling, Julian; Mduda, Joram; Mkindi, Catherine; Mayagaya, Valeriana; Mwakajinga, Grace A.; Nyakyi, Paul T.; Sanga, Valerian L.; Carbery, Dave; White, Leah; Dale, Sara; et al. (Biomedical optics express, 2020)
Optical microscopes are an essential tool for both the detection of disease in clinics, and for scientific analysis. However, in much of the world access to high-performance microscopy is limited by both the upfront cost and maintenance cost of the equipment. Here we present an open-source, 3D-printed, and fully-automated laboratory microscope, with motorised sample positioning and focus control. The microscope is highly customisable, with a number of options readily available including trans- and epi- illumination, polarisation contrast imaging, and epi-florescence imaging. The OpenFlexure microscope has been designed to enable low-volume manufacturing and maintenance by local personnel, vastly increasing accessibility. We have produced over 100 microscopes in Tanzania and Kenya for educational, scientific, and clinical applications, demonstrating that local manufacturing can be a viable alternative to international supply chains that can often be costly, slow, and unreliable.